2004
DOI: 10.1007/s11267-004-3013-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use on Soluble Organic Nitrogen in Soil

Abstract: Although it has been hypothesized that soluble organic nitrogen (SON) plays a central role in regulating productivity in some terrestrial ecosystems, the factors controlling the size of the SON pool in soil remain poorly understood. Therefore our principal aim in this work was to assess the impact of seven different land use systems (rough and managed grassland, deciduous and coniferous woodland, heathland, wetland and tilled land) on the size of the SON and inorganic N (NO − 3 , NH + 4 ) pools in the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Our results indicated that K 2 SO 4 -EON contents ranged from 11.1 to 33.9 mg/kg (dry weight basis) with an average of 21.3 mg/kg. This finding was within the range typically found in agricultural systems in Europe and China (Murphy et al, 2000;Willett et al, 2004;Yang et al, 2007). Generally, K 2 SO 4 -EON contents were lower than K 2 SO 4 -EIN contents; however, they constituted more than 30% of the K 2 SO 4 -TEN pools in the soils.…”
Section: Organic N Component Pools In Soilssupporting
confidence: 86%
“…Our results indicated that K 2 SO 4 -EON contents ranged from 11.1 to 33.9 mg/kg (dry weight basis) with an average of 21.3 mg/kg. This finding was within the range typically found in agricultural systems in Europe and China (Murphy et al, 2000;Willett et al, 2004;Yang et al, 2007). Generally, K 2 SO 4 -EON contents were lower than K 2 SO 4 -EIN contents; however, they constituted more than 30% of the K 2 SO 4 -TEN pools in the soils.…”
Section: Organic N Component Pools In Soilssupporting
confidence: 86%